Gain-Clamped L-Band Erbium-Doped Fiber Amplifier with Co- and Counter-Propagating Lasers - Harun, Sulaiman Wadi; Tamchek, Nizam; Poopalan, Prabakaran; Ahmad, Harith (IOP Publishing, 2003)
The long-wavelength-band (L-band) gain-clamped erbium-doped fiber amplifier with a co- and counter-propagating ring lasers is investigated. The ring laser at 1566nm is formed with a C/L-band wavelength division multiplexing (WDM) coupler. This new technique has shown a good gain-clamping effect with gain variation of less than 0.2 dB for input signal powers from -40 to -14 dBm. Compared with an undamped amplifier, the noise figures for small signals are improved due to the suppression of backward ASE. The amplifier with a co-propagating laser has shown a better gain and noise figure compared to with a counter-propagating laser. The advantage of both gain-clamped systems is that oscillating light does not appear at the output port of the amplifier.